Enhancement of helium exhaust by resonant magnetic perturbation fields at LHD and TEXTOR. (9th August 2016) - Schmitz, O.; Ida, K.; Kobayashi, M.; Bader, A.; Brezinsek, S.; Evans, T.E.; Funaba, H.; Goto, M.; Mitarai, O.; Morisaki, T.; Motojima, G.; Nakamura, Y.; et al.
Abstract: The ability to exhaust helium as the fusion born plasma impurity is a critical requirement for burning plasmas. We demonstrate in this paper that resonant magnetic perturbation (RMP) fields can be used to actively manipulate helium exhaust characteristics. We present results from puff/pump studies at TEXTOR as example for a tokamak with a pumped limiter and from the Large Helical Device (LHD) with the closed helical divertor as example for a heliotron/stellarator device. For LHD, the effective helium confinement time τ p, H e ∗ is a factor of 7–8 higher in the low and high density regimes explored when compared to TEXTOR discharges. This is attributed to ion root impurity transport which is one particular impurity transport regime assessed experimentally at LHD and which facilitates helium penetration to the plasma core. However, when an edge magnetic island is induced by externally applied RMP fields, τ p, H e ∗ is decreased by up to 30 % and hence τ p, H e ∗ values closer to those of TEXTOR can be established. The combination of TEXTOR and LHD results suggest that a magnetic island induced by the RMP field in the plasma source region is an important ingredient for improving helium exhaust. The reduction in τ p, H e ∗ seen is caused by a combination of improved helium exhaust due to an enhanced coupling to the pumping systems, increased outward transport and a reduced fueling efficiency for the helium injected and recycling from the wall elements.